Running on fumes - Dixon, Franklin W. (New York : Aladdin Paperbacks, 2005)
Frank and Joe travel to California where they investigate the leader of a utopian community and his followers to see if they intend to sabotage the oil industry.
008-012.
Keywords: Hardy Boys (Fictitious characters) -- Juvenile fiction; Oil industries -- California -- Juvenile fiction; Sabotage -- Juvenile fiction; Detective and mystery stories -- Juvenile fiction; California -- Juvenile fiction